2005
DOI: 10.1111/j.1462-2920.2005.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanogen communities and Bacteria along an ecohydrological gradient in a northern raised bog complex

Abstract: Mires forming an ecohydrological gradient from nutrient-rich, groundwater-fed mesotrophic and oligotrophic fens to a nutrient-poor ombrotrophic bog were studied by comparing potential methane (CH(4)) production and methanogenic microbial communities. Methane production was measured from different depths of anoxic peat and methanogen communities were detected by detailed restriction fragment length polymorphism (RFLP) analysis of clone libraries, sequencing and phylogenetic analysis. Potential CH(4) production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(147 citation statements)
references
References 57 publications
10
136
1
Order By: Relevance
“…This observation supports a previous study, which showed that Methanoregulaceae was the dominant family in two acidic peatlands (Sun et al, 2012). This family also belongs to the 'Fen cluster' originally detected by Galand et al (2002), and this type of methanogens have later been detected in several Nordic peatlands (Galand et al, 2003;Juottonen et al, 2005;Putkinen et al, 2009). The family belongs to the order Methanomicrobiales, which produces methane by the reduction of carbon dioxide and oxidation of hydrogen (Deppenmeier, 2002;Liu and Whitman, 2008).…”
Section: Increased Nitrogen Loads Drives Plant Composition Towards Vasupporting
confidence: 75%
See 1 more Smart Citation
“…This observation supports a previous study, which showed that Methanoregulaceae was the dominant family in two acidic peatlands (Sun et al, 2012). This family also belongs to the 'Fen cluster' originally detected by Galand et al (2002), and this type of methanogens have later been detected in several Nordic peatlands (Galand et al, 2003;Juottonen et al, 2005;Putkinen et al, 2009). The family belongs to the order Methanomicrobiales, which produces methane by the reduction of carbon dioxide and oxidation of hydrogen (Deppenmeier, 2002;Liu and Whitman, 2008).…”
Section: Increased Nitrogen Loads Drives Plant Composition Towards Vasupporting
confidence: 75%
“…Our study sites also showed relatively lower diversity of the mcrA gene compared to minerotrophic peatlands Juottonen et al, 2005;Merila et al, 2006). Those studies performed a direct comparison between peatland types and found the ombrotrophic sites to have lower methanogen diversity.…”
Section: Increased Nitrogen Loads Drives Plant Composition Towards Vamentioning
confidence: 90%
“…In MES, acetate concentrations were larger, so that further fractionation is feasible. This fractionation should be on the order of less than 10‰ as typical for Methanosaeta (Valentine et al, 2004;Penning et al, 2006), which was the prevailing acetoclastic methanogen in MES (Juottonen et al, 2005) . Therefore, we assumed values of δ 13 C CH 4 −ac being 5-10‰ smaller than δ 13 C org .…”
Section: Resultsmentioning
confidence: 99%
“…These layers exhibited the highest potential CH 4 production rates (Galand et al, 2002). The hydrological conditions and vegetation cover of the sites have already been described in detail (Juottonen et al, 2005). Briefly, MES is a mesotrophic fen, the vegetation of which is a mosaic of lawn and minerotrophic hollow level communities with high diversity.…”
Section: Methodsmentioning
confidence: 99%
“…Syntrophs specifically form obligate mutualistic interactions with methanogens to metabolize organic compounds whose degradation otherwise rapidly becomes thermodynamically unfavorable (DG40) as by-products accumulate (Schink, 1997;Schink and Stams, 2006). Despite such low-energy conditions, engineered and natural methanogenic environments harbor a wide diversity of uncharacterized microorganisms from known phyla and candidate phyla without cultivated representatives (microbial dark matter; Rinke et al, 2013; also see Juottonen et al, 2005;Nemergut et al, 2008;Griebler and Lueders, 2009;Riviere et al, 2009;Glockner et al, 2010;Kong et al, 2010;Kim et al, 2011;Lykidis et al, 2011;Nelson et al, 2011;Rinke et al, 2013). Their presence indicates many undiscovered microbial niches and interactions.…”
Section: Introductionmentioning
confidence: 99%